The COMET initiative database: progress and activities update (2014). Issue 1 (December 2015) - Gargon, Elizabeth; Williamson, Paula; Altman, Doug; Blazeby, Jane; Clarke, Mike
Abstract The COMET Initiative database is a repository of studies relevant to the development of core outcome sets (COS). Use of the website continues to increase, with more than 16, 500 visits in 2014 (36 % increase over 2013), 12, 257 unique visitors (47 % increase), 9780 new visitors (43 % increase) and a rise in the proportion of visits from outside the UK (8565 visits; 51 % of all visits). By December 2014, a total of 6588 searches had been completed, with 2383 in 2014 alone (11 % increase). The growing awareness of the need for COS is reflected in the website and database usage figures.